DIRTY WORDS IN MIKI YOSHIKAWA’S YANKI-KUN TO MEGANE-CHAN COMIC (REVIEW OF LEXICAL FORM) - Abdul Gapur; Rudy Dermawan (Universitas Islam Sumatera Utara (UISU), 2018)
Dirty words are considered as a part of language phenomenon. They have their own forms and categories. This research discusses the Japanese dirty words which is contained in Miki Yoshikawa’s Yanki-kun to Megane-chan comic. it is aimed to describe lexical form in Miki Yoshikawa’s Yanki-kun to Megane-chan comic. This research utilizes descriptive qualitative method. The data research is obtained dirty words in Comic Yanki-kun to Megane-chan comic volume 1. In analyzing the data, theory of Fargo (2007) and Jay (1992) are used to describe lexical form of dirty words. The result of this research reveals that those are five categories out of ten found. There are 9,5% of obscenity, 40% of slang, 3% crusing, 27% of epithets, and 20,5% of scatology. This shows that slang and Epithets are the most used in Miki Yoshikawa’s Yanki-kun to Megane-chan volume 1 comic.